Effectiveness of Destination Branding. The Example of National Tourism Organizations - MARCZAK, Mirosław; BORZYSZKOWSKI, Jacek (Journal of Environmental Management and Tourism; Vol 11 No 4 (2020): JEMT Volume XI Issue 4(44) Summer 2020DO - 10.14505//jemt.v11.4(44).01, 2020)
Branding is considered to be the most effective way to improve the quality of operations undertaken in numerous sectors of economy. It also plays an important role in creating images of many tourist destinations. National Tourism Organizations (NTOs) are responsible for that task in particular countries. The main aim of the article is an attempt at providing a simplified evaluation of effectiveness related to operations (or operation fields) undertaken by NTOs in the process of brand management at the national level, especially activities undertaken in favor of brand development. The main effectiveness measure is a medium-term rate of the change in the number of tourist visits in countries where the analyzed NTOs were operating in the years of 2007-2017. The analysis includes 81 organizations. The basic tool applied for the research is a questionnaire form and the whole process of data collection, data verification and the comparative statistical analysis is completed in six stages. The research indicates the significant role of branding among the operations undertaken by the analyzed organization. It also indicates the fact that branding is an efficient and indispensable element in the process of destination brand management at the national level. The results of the research confirm the fact that the analyzed organizations consider branding as one of their most effective activities aimed at encouraging the highest number of foreign tourists to visit their countries.